Study of Antimicrobial Activity of Abutilon pannosum Choline Chloride Based Extraction as Meat Preservatives - Elsharawy, Nagwa T. (Journal of Advanced Veterinary Research, 2023)
Meat industry preservation methods to extend the shelf life and maintain the microbial safety of meat products. There is big shortage in research that conducting examination of the antimicrobial activity of Abutilon pannosum choline chloride based extracts (APCCBE). This study aimed to assess the efficacy of APCCBE in inhibiting the growth of common meat pathogens, investigated the potential impact of APCCBE treatment on the meat products shelf life. The polar fraction of Abutilon pannosum leaves fine powder was obtained via a solid-liquid extraction, GC-MS analysis, Antibacterial activity of fresh APCCBE was performed against four strains of microorganisms: Staphylococcus aureus, Escherichia coli, Bacillus subtilis using Muller Hinton and six antibiotics discs (50 mg/mL) as follows; “Cefoxitin (FOX), Cephalothin (KF), Cotrimoxazole (TS), Gentamicin (GM), Augmentin (AUG) and Ampicillin (AP). Determination of the storage period of meatballs using packages containing APCCBE were each 100g of meatballs were wrapped by each package film concentration, stored in dark and cool conditions and compared with meatballs wrapped by uncoated PE film package. the study has declared that the APCCBE possess efficient antimicrobial effects against the test bacterial strains. These findings provide valuable knowledge in pathogenic bacteria treatment and food preservation, in addition to its ability in extension the shelf life of the chilled meatballs to about 2 weeks instead of 5 days only in case of control meatballs before and after cooking. Further research is needed to achieve the best application and usage of the extractions of APCCBE.